Informed Consent in Contrast-Enhanced CT: Understanding of Risks and Identification of Possible Prognostic Factors - Röhrl, S.; Dendl, L. M.; Scharf, G.; Zeman, F.; Stroszczynski, C.; Schreyer, A. G. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: Aim of our study was to assess understanding of risks associated with intravascular application of contrast media in patients undergoing CT examination. We wanted to evaluate epidemiologic and socio-economic prognostic factors for a higher understanding of risks. Additionally, we evaluated a possible correlation between an extensive, outcome-oriented oral informed consent and better understanding of risks.Materials and Methods: 120 patients distributed in 2 study arms participated in this prospective study. In study arm I, the treating physician was not informed that his patients participated in a study whereas the physician in study arm II knew about the survey. After the informed consent we performed a standardized, semi-structured interview to enquire the 3 most frequent risks of intravascular application of contrast agents (anaphylactoid reactions, nephropathy and thyrotoxic crisis) and epidemiologic data. The understanding of the risks was evaluated using a 6 point scale.Results: Patients scored 3.73 points in study arm I and 4.93 points in arm II on average. The statistical difference between both study arms was highly significant (p <0.001). In a combined logistic regression analysis, only “higher education” (p = 0.001) and participation in study arm II (p =0 .001) showed a significant connection to a better understanding of risks.Conclusion: Patients profit from an outcome-oriented and individualized informed consent. Due to the significant correlation between educational level and understanding of risks, informed consent should be adjusted to the educational status of the individual patient, e. g. by using didactic aids or individualized information sheets.Key points:• The understanding of risk factors is better in patients with a higher educational level.• Repetitive examinations do not lead to a better understanding of risks.• A result-oriented pre-examination discussion leads to a better understanding of risk factors.Citation Format:• Röhrl S, Dendl LM, Scharf G et al. Informed Consent in Contrast-Enhanced CT: Understanding of Risks and Identification of Possible Prognostic Factors. Fortschr Röntgenstr 2015; 187: 973 – 979
Keywords: informed consent; understanding of risks; contrast agent